A EFEKTIVITAS EKSTRAK KAYU SECANG KOMBINASI AMOKSISILIN TERHADAP MRSA - Besse Yuliana; Husnil Ania; Habiburrahim (Jurnal Penelitian Pendidikan IPA, 2025)
Bacterial resistance to antibiotics is a global health threat, with Methicillin-Resistant Staphylococcus aureus (MRSA) as one of the most deadly pathogens. MRSA is resistant to methicillin and other β-lactam antibiotics, causing therapy failure and increased mortality up to 64% higher than non-resistant bacterial infections. This condition urges the development of new therapeutic strategies. This study focuses on sappan wood (Caesalpinia sappan L.), which is rich in compounds such as brazilin (the main component), flavonoids, and tannins, which have been reported to have significant antibacterial activity against various Gram-positive and Gram-negative pathogenic bacteria, including Staphylococcus aureus. Brazilin, a flavonoid, specifically exhibits inhibitory activity against MRSA. Based on the urgency of MRSA resistance and the pharmacological potential of sappan wood, this study aims to test the effectiveness of sappan wood isolation combined with amoxicillin against MRSA. The research method is a laboratory study that focuses on extract preparation, compound isolation, and in vitro antibacterial activity testing. The core results of the study showed that sappan wood extract (Caesalpinia sappan L.), which was identified to contain active compounds such as brazilein, was successfully extracted with a yield of 10.15%. Most importantly, the combination of sappanwood extract with amoxicillin showed a strong synergistic effect, as evidenced by the large inhibition zone diameter (up to 30.40±0.75 mm) against MRSA bacteria.